Formulation Development and Evaluation of Fast Dissolving Sublingual Film of Apixaban: Design of Experiment-Based Approach - Kanugo, Abhishek; Adnan, Mohammad (Indian Journal of Pharmaceutical Education and Research)
Objectives: The benefits of the active ingredients are circumvented due to poor bioavailability or presystemic metabolism. Apixaban is an oral anticoagulant possessing high lipophilicity and bioavailability of less than 50%. This drawback can easily be overcome with the help of a sublingual route of administration in the form of the oral thin film. The present research was carried out to improve Apixaban solubility, bioavailability, and therapeutic efficacy. Materials and Methods: The compatibility of Apixaban with the HPMC E15 (film former) was assessed with FTIR, DSC, and crystallinity with XRD. The quality-by-design approach was implemented with 3 independent factors such as concentration of HMPC E15, PEG 400, and cross-povidone. The disintegration time and cumulative percentage of drug release were recognized as critical quality attributes. Results: The ANOVA model predicted 0.0017 and 0.03111 p-values for disintegration and dissolution, respectively, indicating a significant model. The optimized batch F11 disintegrated within 15 sec, and 99.11% of the drug was released. The surface morphology was estimated with a scanning electron microscope. Compared with the marketed tablet formulation (70 min), the developed sublingual film was released completely within 10 min. Hence, the sublingual film of Apixaban is highly preferred in the prevention and treatment of deep vein thrombosis and pulmonary embolism. Conclusion: The sublingual film of Apixaban reflected an enormous rise in solubility, thereby attaining bioavailability.
Keywords: Oral thin film; Apixaban; HPMC E15; Box-Behnken Design; Deep vein thrombosis; Pulmonary embolism.